Nanoparticle ferritin-bound erastin and rapamycin: a nanodrug combining autophagy and ferroptosis for anticancer therapy. (18th June 2019) - Li, Yaoqi; Wang, Xinyu; Yan, Junjie; Liu, Yu; Yang, Runlin; Pan, Donghui; Wang, Lizhen; Xu, Yuping; Li, Xiaotian; Yang, Min
Abstract : The intracellular autophagy-mediated ferroptosis-induction process by the NFER nanodrug assembled by ferritin, erastin, and rapamycin. Abstract : Ferroptosis and autophagy are the two forms of the regulation of cell death that play important roles in cancer therapy. However, little is known about the combination of the therapeutic effects of ferroptosis and autophagy in cancer therapy. Here, in this study, we constructed a novel carrier-free nanodrug called nanoparticle ferritin-bound erastin and rapamycin (NFER). The NFER nanodrug was prepared by the emulsification technique; it exhibited an average size of 78.8 nm and zeta potential of −25.9 ± 3.3 mV. Controllable drug encapsulation efficiency and loading ratios in NFER could be obtained. This nanodrug showed high stability in both water and PBS for several days. The release studies demonstrated that rapamycin and erastin could reach equilibrium after 24 h and 36 h, respectively; the maximum values of the released percentages of both reached beyond 30%. An in vitro study revealed that NFER showed robust ferroptosis-inducing capability by the downregulation of glutathione peroxidase-4 (GPX4) and lipid peroxidation accumulation. The autophagy process induced by rapamycin in NFER also played an important role in strengthening ferroptosis. The selective cancer cell killing ability of NFER was verified in cancer cells and normal cells. The ferroptosis-induced cytotoxicity was confirmed through several ferroptosis and autophagy inhibitors. Furthermore, the NFER nanodrug showed an improved control of tumor recurrence in the 4T1 tumor resection model. In summary, these results demonstrated that NFER exhibited excellent properties as a nanodrug, and the cell death induced by NFER was through an autophagy-associated ferroptosis pathway. This study based on protein nanodrug-induced autophagy-associated ferroptosis would provide a new insight into cancer therapy.